SEBARAN KEKERINGAN HIDROLOGI BERDASARKAN DEBIT ALIRAN DI KABUPATEN BIMA - I WAYAN YASA; AGUSTONO SETIAWAN; I DEWA GEDE JAYA NEGARA; HUMAIRO SAIDAH; ANNISA HUMAYRA DIRGANTARA (Universitas Mahasaraswati K. Mataram, 2023)
A phenomenon that often occurs in Indonesia which is also an annual disaster that hit several areas is drought. Drought is a condition in which an area, land, or community experiences a shortage of water so that it cannot meet their needs. Drought can be caused because an area does not experience rain or is dry for a long period of time or the rainfall is below normal, so that the water content in the soil is reduced or even non-existent. The areas to be analyzed are the Hidirasa watershed, the Rontu watershed, and the Jangka watershed in Bima Regency, West Nusa Tenggara. The analysis drought aims to determine the deficit, drought duration, drought criteria based on deficits and surpluses that occur by analogy to Oldeman's criteria, hydrological drought index analysis, and hydrological drought distribution maps. In this study, data were used for the Tawali watershed in the Hidirasa watershed, the Sari watershed for the Jangka and the Kumbe water for the Rontu watershed to determine the Q50 and Q80 thresholds using the method Flow Duration Curve (FDC) to obtain hydrological drought characteristics. In the analysis of hydrological drought in several watersheds in Bima Regency, the results show that the maximum deficit in the Hidirasa, Term and Rontu watersheds was 1.09 m³/s, 0.14 m³/s, 0.49 m³/s which occurred in 2001, 1995, and 2001. From the deficit, it was found that the average drought period occurred 8-9 months from May to December and even some until January which indicated that the drought criteria were in zone 2 according to Oldeman. The largest hydrological drought index is the Hidirasa watershed, the Jangka Watershed and the Rontu watershed, respectively, -0.45, -1.00, -1.00, with a very strong drought category.